The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.neuro.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Trace amine-associated receptor 1 regulation of methamphetamine-induced neurotoxicity

Abstract: Trace amine-associated receptor 1 (TAAR1) is activated by methamphetamine (MA) and modulates dopaminergic (DA) function. Although DA dysregulation is the hallmark of MA-induced neurotoxicity leading to behavioral and cognitive deficits, the intermediary role of TAAR1 has yet to be characterized. To investigate TAAR1 regulation of MA-induced neurotoxicity, Taar1 transgenic knock-out (KO) and wildtype (WT) mice were administered saline or a neurotoxic regimen of 4 i.p. injections, 2 hr apart, of MA (2.5, 5, or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 89 publications
(128 reference statements)
2
29
0
Order By: Relevance
“…In animals with decreased TAAR1 levels either due to KO (Di Cara et al, 2011;Achat-Mendes et al, 2012;Sukhanov et al, 2016) or an endogenous defunctionalizing mutation (Harkness et al, 2015;Reed et al, 2018), increases in acquisition and retention of conditioned place preference (CPP) (Achat-Mendes et al, 2012), hyperlocomotion (Achat-Mendes et al, 2012;Sukhanov et al, 2016), reinstatement (Sukhanov et al, 2016), self-administration (Harkness et al, 596 Reed et al, 2018), and toxicity (Miner et al, 2017), along with decreased autoinhibitory effects (Di Cara et al, 2011), were seen in response to either amphetamine, methamphetamine, or 3,4-methylenedioxymethamphetamine (MDMA). Such effects suggested that TAAR1 agonists may be beneficial in reducing the abuse potential of amphetamines and TAAR1 agonists have now been confirmed to decrease the behavioral sensitization, self-administration, reinstatement, drug-seeking behavior, and withdrawalinduced impulsivity observed in response to methamphetamine administration (Jing et al, 2014;Cotter et al, 2015;Pei et al, 2017;Xue et al, 2018).…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 99%
“…In animals with decreased TAAR1 levels either due to KO (Di Cara et al, 2011;Achat-Mendes et al, 2012;Sukhanov et al, 2016) or an endogenous defunctionalizing mutation (Harkness et al, 2015;Reed et al, 2018), increases in acquisition and retention of conditioned place preference (CPP) (Achat-Mendes et al, 2012), hyperlocomotion (Achat-Mendes et al, 2012;Sukhanov et al, 2016), reinstatement (Sukhanov et al, 2016), self-administration (Harkness et al, 596 Reed et al, 2018), and toxicity (Miner et al, 2017), along with decreased autoinhibitory effects (Di Cara et al, 2011), were seen in response to either amphetamine, methamphetamine, or 3,4-methylenedioxymethamphetamine (MDMA). Such effects suggested that TAAR1 agonists may be beneficial in reducing the abuse potential of amphetamines and TAAR1 agonists have now been confirmed to decrease the behavioral sensitization, self-administration, reinstatement, drug-seeking behavior, and withdrawalinduced impulsivity observed in response to methamphetamine administration (Jing et al, 2014;Cotter et al, 2015;Pei et al, 2017;Xue et al, 2018).…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 99%
“…46 Some studies have suggested that the maintenance of drug intake and relapse to drug intake after forced abstinence, are associated with functional switches of monoaminergic and glutamatergic systems. However, because mice with functional TAAR1 will not voluntarily consume MA, 41 a forced exposure model would be required to study this, as has been used to examine the role of TAAR1 in sensitivity to MA-induced neurotoxicity.…”
Section: Experiments 3: Depression-like Symptoms After Prolonged Formentioning
confidence: 99%
“…However, because mice with functional TAAR1 will not voluntarily consume MA, 41 a forced exposure model would be required to study this, as has been used to examine the role of TAAR1 in sensitivity to MA-induced neurotoxicity. 46 Some studies have suggested that the maintenance of drug intake and relapse to drug intake after forced abstinence, are associated with functional switches of monoaminergic and glutamatergic systems. 29,[47][48][49] Microdialysis studies reported higher basal levels of serotonin in the nucleus accumbens (NAc) of MAHDR mice, compared to MALDR mice, as well as resistance in MAHDR mice to MA-induced elevations of serotonin in the medial prefrontal cortex that occurred in MALDR mice.…”
Section: Experiments 3: Depression-like Symptoms After Prolonged Formentioning
confidence: 99%
“…The trace amine-associated receptor 1 (TAAR1) is a Gcoupled receptor expressed in the monoaminergic regions of the brain (Lam et al, 2018). When activated by appropriate ligands including methamphetamine, dopaminergic function is modulated (Miner, Elmore, Baumann, Phillips, & Janowsky, 2017). Amphetamine also has actions at the acetylcholine, serotonin, opioid, and glutamine receptors, and increases blood flow in the brain (Faraone, 2018).…”
Section: Namementioning
confidence: 99%